Are Multiwavelength Variability Events in Blazars Driven by a Common Stochastic Process? - Jingran Xu; Shaoming Hu; Xu Chen; Shifeng Huang (The Astrophysical Journal)
We investigate the underlying stochastic processes driving the multiwavelength variability of the blazar BL Lacertae over the past two decades. Observations from Weihai Observatory over 224 nights reveal that the power spectral slopes of intra-night variability follow a Gaussian distribution, ranging from approximately 0.4–2.6, with an average trend consistent with the long-term variability power spectrum. Using power spectral analysis methods, such as the classical periodogram and the Lomb–Scargle periodogram, in combination with modeling techniques such as the power spectral response method, the multiple fragment variance function, and the continuous time autoregressive moving average, we study the multiband power spectral characteristics across a wide range of timescales (∼7 dex). The results demonstrate that, at lower frequencies, the power spectral density across different bands shows remarkable consistency, suggesting that these variations may be driven by a common stochastic process related to the accretion disk. However, significant discrepancies arise at higher frequencies, indicating the presence of multiple stochastic processes. We propose that the variability is governed by at least two distinct processes: one related to disk stochastic processes, dominating the long-term variability, and another associated with jet stochastic processes, which may result from turbulence, particle acceleration, and shock interactions within the jet, and drive the short-term, high-frequency variations. These findings provide unique insights into the complex mechanisms underlying blazar variability and suggest an intrinsic connection between the accretion disk and jet dynamics.